Characterization of a-Si:H Solar Cell Modules on Plastic Substrates by High Resolution LBIC Technique. (December 2015) - Fernandes, M.; Vygranenko, Y.; Vieira, M.; Sazonov, A.; Yang, R.; Khosropour, A.
Abstract: This article reports on characterization of hydrogenated amorphous silicon (a-Si:H) photovoltaic modules fabricated on 100 μm thick PEN plastic films. Experimental results show that the shunt leakage is one of the factors reducing the device performance. Current-voltage characteristics of individual a-Si:H p-i-n cells were analysed to estimate a variation of shunt resistances. A SPICE model of the a-Si:H p-i-n cell with local shunt leakage was also developed to analyse the impact of leakage currents on the device performance. Using the LBIC technique, the presence of multiple shunts in the cell was detected. They are attributed to surface defects in plastic foils, which are thermally induced during the device fabrication.